Theoretical justification of utilization of forest waste by incineration in a composition of bio-water-coal suspensions. Ignition stage. (April 2020) - Kuznetsov, G.V.; Syrodoy, S.V.; Malyshev, D.Yu.; Gutareva, N.Yu.; Nigay, N.A.
Highlights: The ignition of particles of a bio-coal-water slurry has been studied. Fuel was prepared from coal, water and forest waste. We found that forest biomass significantly improves the ignition process. We have developed a new mathematical model for the ignition of particles of bio-carbonic fuel. Theoretical and experimental results showed a good agreement. Abstract: The results of the theoretical studies of the ignition processes of a completely new class of fuel for thermal power plants—Bio-water-coal fuel (Bio-WCF) based on coals of varying degrees of metamorphism, water and forest waste (forest combustible fuel – FCM) have been presented. A mathematical model of the processes of heat and mass transfer that occur during the induction period of time has been developed. The model differs from the known ones in a detailed description of the kinetics of the physicochemical processes occurring in the boundary layer and in the particle. The numerical simulation of the ignition process has been carried out and the ignition delay times (tign ) have been calculated. According to the results of the theoretical studies, the influence of the kinetics of gas-phase reactions proceeding in the induction period of time has been established. It has been shown that OH radicals can be active centers-catalysts of the chemical reactions of ignition and combustion of hydrogen (H2 ), methane (CH4 ) and carbon monoxide (CO). The basic laws of the physicochemical processes occurring on the surface of a particle (after evaporation of moisture) of Bio-water-coal fuel have been established. It has been shown that secondary reactions of incomplete oxidation of carbon by atmospheric oxygen (with the formation of CO), water vapor (with the formation of CO (or CO2 ) and H2 ), hydrogen (with the formation of CH4 ) do not significantly affect the particles ignition characteristics and conditions (maximum deviations of the values ignition delay times do not exceed 6%).